THE PURSUIT OF CREDIBILITY: A NARRATIVE SYNTHESIS OF GOVERNANCE AND GLOBAL TRENDS IN WASTE MANAGEMENT DISCLOSURE - M. Ja’afar, Noor Faiza; Zulkifli , Nor Adila; Mohamad, Maslinawati (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2026)
Corporate waste management disclosure has become a critical nexus of accountability in the circular economy; however, concerns persist over its credibility and susceptibility to greenwashing. This narrative review synthesises the literature to critically examine the governance mechanisms, global regulatory trends, and assurance practices that shape the evolution of waste-related reporting. This review of scholarly work in accounting, governance, and sustainability studies identifies five interconnected themes: the contested efficacy of assurance design, the role of mandatory regulation as a catalyst, governance structures as antecedents, the symbolic-substantive disclosure spectrum, and the powerful moderating influence of contextual factors. A key insight is that disclosure quality is not a linear output but an emergent property of the alignment or misalignment between internal governance capability, external regulatory pressure, and mediating assurance processes. Major contradictions are found in the assurance value proposition, where it signals credibility but often fails to verify forward-looking claims or methodologically robust data, and in a pronounced Global North research bias that limits theoretical generalisability. Theoretically, this review contributes an integrative framework that positions legitimacy, institutional, and agency theories as complementary. In practice, this implies that regulators must mandate not only assurance but also its specific design (level, scope, methodology) to combat greenwashing effectively. Future research must adopt configurational and process-oriented methodologies, such as Qualitative Comparative Analysis (QCA) and ethnographic studies of the assurance nexus, particularly in under-researched emerging economies, to close the identified gaps between disclosure form and function.